Pemodelan Debit Banjir Sungai Cimoyan Kabupaten Serang - Banten - Sulwan Permana; Abdal Azziz (Jurnal Konstruksi, 2025)
Flooding is defined as the overflow of water in large quantities. It is caused by heavy rainfall, land surfaces being lower than river or sea levels, locations situated in basins surrounded by mountains, and low water absorption capacity. Like many rivers in Indonesia, the Cimoyan River is experiencing severe degradation. Population growth and economic development have led to land-use changes in the watershed (DAS) area. As a result, there has been an increase in peak flood discharge, erosion, landslides, and a decline in baseflow. Additionally, the river faces problems such as waste accumulation, sediment buildup, and human settlement along its banks. Flooding in the Cimoyan River has inundated hundreds of homes in the area, causing significant economic losses including property and infrastructure damage. Downstream communities often suffer crop failures due to the river’s overflow. The purpose of this study is to determine the design flood discharge using the Nakayasu and Snyder synthetic unit hydrograph (HSS) methods for the Cimoyan River. The method used in this study to assess the cross-sectional capacity of the Cimoyan River through HEC-RAS software is a quantitative approach. Thus, the quantitative data were analyzed using statistical techniques. Based on hydrological analysis, the peak flood discharge using the Nakayasu method (Q100) is 813.97 m³/s, occurring at 02:45, while the peak discharge from the Snyder method (Q100) is 484.61 m³/s at 06:29. The cross-sectional capacity of the Cimoyan River, as calculated with HEC-RAS, shows that most sections of the river are safe from overflow.